The default context and Pragmatic interpretation Reading during the reign of Imam Ali (p.b.n.m) to MalikAL-Ashtar - طارش حاتم حازم (Al-Adab Journal, 2018)
Speech is born by the context and it has not value without context. and The changing that happen in tactics speech facility context there for speech construction must know the context so that it one of the context in which recourse to it the issue by forcing the issue to the recipient calls for the case to be substantiated or veto the receiver read the case in the in the light of exegesis deliberative because he realize that the issue presented is not intended but which produce the resulting report on issue imposed by appropriate so the receiver when came to the result . the reading has two sides . the speaker and the receiver in the light of those reading . we will read the reign of Imam Ali to achieve this in the mind of the receiver present malekashtar – the cosmic and the receiver – general reader